Impact of chronic infections (periodontic and endodontic) in implant dentistry - Bhumanapalli Venkata Ramesh Reddy; Swetha Tanneeru (Wolters Kluwer Medknow Publications, 2015)
Dental implant plays an important role in oral rehabilitation. In recent decades, the concept of restoratively driven implant placement has become well-accepted. Thus, an increasing number of patients, especially those with past or present periodontitis or with periapical infections, desire to receive dental implants to restore their lost teeth. This review discusses the relationship between chronic periodontal and periapical infections with periimplantitis, with a focus on implant outcome. The studies considered for the inclusion were searched in MEDLINE (pubmed). The search was restricted to studies published in English from 1980 to 2015. Screening of eligible studies and data extraction were carried out by the reviewers. The articles included in the review comprised in vitro studies, in vivo studies (animals and humans), abstracts, and review articles.